Revenue Generation Trends through Sharing and Grants An Evidence from Baglung Municipality, Gandaki Province, Nepal - Silwal, Sudarshan (Dhaulagiri Journal of Contemporary Issues, 2024)
This paper assesses the trends of revenue generation through sharing and grants in Baglung Municipality from fiscal year 2018/19 to 2022/23. The data were gathered from a comprehensive review of financial reports, budgetary documents, revenue sharing agreements, and relevant records of the municipality, and from the opinions of the respondents using five-point Likert scale questionnaires, selecting 42 respondents from 14 wards of Baglung Municipality purposively. The obtained data were analyzed descriptively. The study shows variations in the revenue performance. This municipality has been found primarily dependent on value-added tax (VAT) revenue (54.18 % in an average), which regularly accounts for a sizable share of revenue sharing, even though revenue from real estate registration fees shows a constant increase and contributes to overall revenue sharing. Regarding grants, the allocation among different categories indicates a strong focus on equalization grants (covered 21.72 % in federal grant and 66.75 % in province grant in an average). Similarly, the study has found a turnover or new wave of representatives (69.0 % less than two years of involvement) within the local entity. The study result also indicates the multifaceted needs of the community, with a particularly strong focus on roads and water supply as per the responses of 59.5 % respondents. The current revenue sharing model promotes local development, and the distribution of revenue among different sectors is found effective. Finally, this study suggests strategies pertaining to revenue estimation methodologies, manpower planning initiatives, mitigation of risks associated with an overreliance on VAT, decisions based on needs, integration of community feedback, and diversification of revenue sources to foster long-term financial stability of this municipality.